The Change of Public Individual Prevention Practice and Psychological Effect From the Early Outbreak Stage to the Controlled Stage of COVID-19 in China in 2020: Two Cross-Sectional Studies - Han, Bingfeng; Liu, Hanyu; Zhao, Tianshuo; Liu, Bei; Zheng, Hui; Wan, Yongmei; Cui, Fuqiang (Frontiers in Psychology, 2021)
Background: COVID-19 broke out in China and spread rapidly in January and February 2020. Following the prevention and control measures of the Chinese government, the outbreak was gradually brought under control after March. The changes in people’s attention to the epidemic, individual prevention practice and psychological effect from the early outbreak stage to the under controlled stage need to be evaluated. Methods: Two cross-sectional, population-based online surveys were conducted from January 28 to February 1 2020 and from February1 to March 18 2020. Socio-demographic information and individual protective practice were collected and the State-Trait Anxiety Inventory (STAI) was used for measuring anxiety. The range of STAI score was 5-25, and the higher the score, the more anxious it was. The respondents of the two surveys were matched on a one-to-one basis according to their province, gender, age, education, and marriage. Wilcoxon signed ranks test and Mann-Whitney U test were used to compare STAI score changes in two stages and in different demographic characteristics. Results: We included 9 764 individuals in the first survey and 1 669 in the second survey, covering 30 provincial administrative regions in Mainland China. COVID-19 has affected almost every aspect of people’s normal life, especially lifestyle. The proportion of people who paid attention to it every day had dropped from 97.6% to 88.9%. We identified that vast majority people wore masks when they went out. The proportion has declined from 96.5% to 92.4% for hand hygiene and from 98.4% to 95.3% for not attending parties. People’s anxiety (STAI score) across the country has decreased from a median of 19 in the early outbreak stage to a median of 12, including people with all demographic characteristics, but some have increased in 16 provinces. Conclusions: People’s attention to information about the epidemic has declined slightly, but a high proportion of people maintained good practices such as wearing masks, hand hygiene, and not attending parties. People’s anxiety had generally declined from the early outbreak stage to the under controlled stage, but it was still at a high level.